Evidence of moderate degree of capital mobility in 15 Caribbean countries and the absence of the Feldstein-Horioka (F-H) puzzle - Wright, Allan S....[et al.] ([Caribbean Centre for Money and Finance] [St. Augustine]TT, 2009)
Explores the connection between saving and investment among 15 Caribbean countries for the period 1960-2008.